BABUR'S WORK AS A PHILOSOPHY OF ETHICS AND LOVE - Khamdamov Bekhzod Khabibovich (Web of Journals Publishing, 2024)
In this article, the author analyzed and described the sociocultural and scientific environment of Transoxiana and India in the 16th-17th centuries. The reasons for the stability and prosperity of the Mughal state, and the collapse of the empire. The author identifies the factors for the remarkable growth of the culture of the Mughal Empire.
Keywords: Great Mughals, heyday, fragmentation, centralization, empire, culture.